(untitled) (Research, Society and Development, 2020)
Objective: To discourse the stigma faced by users, as well as family difficulties and the importance of therapeutic follow-up for their recovery. Methodology: Unveils an integrative review of the literature developed with articles published and indexed in the Virtual Health Library (VHL). Results and Discussion: Of the 34 articles resulting, after applying the inclusion, exclusion criteria and analysis of their contents, 10 were selected for this study. Three thematic groups were identified, namely: Facing the stigma experienced by users of psychoactive substances, Unfamiliar family pattern resulting from addiction and Harm reduction strategies for this audience. Conclusion: alcohol and drug users experience several stigmas that make them excluded from society, with the inclusion of these users in health services, in a humanized way, with the purpose of obtaining effective results in their treatment and the family bond and of great importance and social, thus reducing the high rates because it concerns a setback with regard to public health.